Analysis of The State of Educative Workers in Polytechnic of Agricultural (STPP) Lecturers Based on Empirical Data in Sumatera Utara - Nurliana Harahap; Ameilia Zuliyanti Siregar; Yuliana Kansrini (Jurnal Pertanian Tropik, 2019)
The objectives of the study are determined to analyze the competencies, motivation and implementation of lecturers in improving performance. This research was conducted in 4 STPPs from 6 service education colleges under the Ministry of Agriculture namely Medan STPP, Bogor STPP, STPP Magelang and STPP Malang. The research area was chosen purposively with the consideration that the six locations were universities belonging to the Ministry of Agriculture which had received performance allowances since 2012. The researchers wanted to determine how the level of performance capabilities of government officials (PNS) especially lecturers in producing quality graduates. Lecturer competencies have a significant influence on the performance of lecturers. This indicates that the higher the competence possessed by the lecturer, the higher the performance of the lecturer. Lecturer competency consists of four types of competencies, namely pedagogic competence, social competence, professional competence and personality competencies. Based on purposively methods, the results of research in 4 (four) STPP, social competency is the ability to communicate and interact effectively and efficiently with students, fellow teachers, parents / guardians of students, and the wider community having the highest influence of 34.6%, then competency professional, ability in mastering subject matter widely and deeply, that is equal to 23.2%. Providing performance allowances which is one form of the reward and punishment system and provides a significant influence on the performance of the Lecturer.Motivation has no significant effect on the performance of the Lecturer in Agricultural Extension College (STPP).